Occlusal Splint Therapy for a Dysfunctional Temporomandibular Joint - Jagtap, Amit; Shadakshari, Shivamurthy; Swamy, KN Raghavendra; Bora, Neelam (Journal of Orofacial Research, 2014)
Splint therapy is an effective form of treatment for the pain of many types of temporomandibular disorders and bruxism. There are many unanswered questions as to how splints work. This article is a review of the literature which focuses on an effective splint design for the different degrees of temporomandibular problems.